INCLUSIVE GROWTH AND MOTHER TONGUE AS MEDIUM OF INSTRUCTION AS ADVOCATED BY NATIONAL EDUCATION POLICY (NEP 2020) - Bhatia, Rajiv (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Gandhiji was not technically an educationist like Tagore or Aurobindo but his view on basic education testifies to the fact that he was a social educator. He advocated social revolution (reform) to go hand in hand with any political revolution and education is an important means to bring about any social revolution and reform. His educational ideas are summarized as Education of children upto 14 years of age should be free, compulsory and universal. Mother tongue should be the medium of instruction and English should not be given any importance in the curriculum. Making the people literate is not making them educated, education is a much higher process. It should develop human values in the child and should enable the child to realize the ultimate truth (God) through non violence and purity of means. Education should develop all powers of the child to adjust in the community to which he belongs. Education should develop the total personality of child, his mind, body and soul. To enable the child to earn his living, craft should be the medium of instruction. It is a must for the economic self reliance of the child. These crafts should be related with the local industries, i.e., the crafts for a child should be locally chosen. The main aim of basic education is to purify the heart and mind of the people and create a society free from all exploitations and aggressions. Child should also be given work experience through practical training. Theoretical knowledge without getting it into practice is useless. Schools should be made a place of activity for the child. All work experiences should be given to the child in schools. Education should make responsible, useful and dynamic citizens. Inculcation of universal moral values through education in the child is the pre-requisite for achieving any success in the field of education. Mahatma Gandhiji believed in a classless society by decentralizing powers to village panchayats and parishads and by raising the economic standard of lower sections of the society. He wanted to create exploitation free society by increasing the employment opportunities for the poor. His socialism is different from that of Marx in the sense that Marx believed in the supremacy of matter while Gandhiji was the staunch supporter of spiritualism. Other differences between the two are given as he did not believe in the incumbency of class struggle like Marx. He did not believe that state’s ownership of means of production would end exploitation. In spite of these he had a strong faith in socio-economic equality of man.